Numerical simulation of inductive heating in thermoplastic unidirectional cross-ply laminates - de Wit, A. J.; van Hoorn, N.; Straathof, L. S.; Vankan, W. J. (Frontiers in Materials, 2023)
Thermoplastic Composites can be re-melted allowing them to be joined via welding. This is an attractive alternative to conventional methods that are used to join thermoset composite parts such as mechanical fastening and adhesive bonding. In this work the inductive heating of uni-directional (UD) plies of thermoplastic carbon fiber reinforced polymer (CFRP) laminates is investigated. The focus is on developing a numerical electromagnetic and thermal simulation model that captures the main processes involved in eddy current generation and heat generation, in particular in the interface areas of the UD plies. A measurement technique has been developed to obtain the electric properties of the ply material. Furthermore, to support the modelling of both the induction heating equipment and work piece a field measurement of the magnetic field surrounding the coil and work piece has been developed. Inductive heating experiments were carried out on several thick composite laminate plates with different ply lay-ups to compare and validate the electro-magnetic-thermal simulation model. The measured surface temperatures were compared with the results from the simulation model. The results of this work can be used to support the design of UD-ply laminates to improve their ability to be welded via inductive heating. In addition, the results of this work can be used to assist in pre-determining induction welding equipment settings and heating times.